Real-world data of tenecteplase vs. alteplase in the treatment of acute ischemic stroke: a single-center analysis - Yao, Yu; Wu, Yuefei; Zhang, Xiaoqin; Liu, Chang; Cai, Lingling; Ying, Yisha; Yang, Jianhong (Frontiers in Neurology, 2024)
Background This retrospective observational cohort study aimed to evaluate whether tenecteplase’s use for acute ischemic stroke (AIS) has time management advantages and clinical benefits. Methods 144 AIS patients treated with alteplase and 120 with tenecteplase were included. We compared baseline clinical characteristics, key reperfusion therapy time indices [onset-to-treatment time (OTT), door-to-needle time (DNT), and door-to-puncture time (DPT)] and clinical outcomes (24-h post-thrombolysis NIHSS improvement, and intracranial hemorrhage incidence) between the groups using univariate analysis. We assessed hospital stay durations and used binary logistic regression to examine tenecteplase’s association with DNT and DPT target times, NIHSS improvement, and intracranial hemorrhage. Results Baseline characteristics showed no significant differences except hyperlipidemia and atrial fibrillation. OTT (133 vs. 163.72, p = 0.001), DNT (36.5 vs. 50, p < 0.001) and DPT (117 vs. 193, p = 0.002) were significantly faster in the tenecteplase group. The rates of DNT ≤ 45 min (65.83% vs. 40.44%, p < 0.001) and DPT ≤ 120 min (59.09% vs. 13.79%, p = 0.001) were significantly higher in the tenecteplase group. Tenecteplase was an independent predictor of achieving target DNT (OR 2.951, 95% CI 1.732–5.030; p < 0.001) and DPT (OR 7.867, 95% CI 1.290–47.991; p = 0.025). Clinically, the proportion NIHSS improvement 24 h post-thrombolysis was higher in the tenecteplase group (64.17% vs. 50%, p = 0.024). No significant differences were observed in symptomatic intracranial hemorrhage (sICH) or any intracranial hemorrhage (ICH). Patients receiving tenecteplase had shorter hospital stays (6 vs. 8 days, p < 0.001). Tenecteplase was an independent predictor of NIHSS improvement at 24 h (OR 1.715, 95% CI 1.011–2.908; p = 0.045). There was no significant association between thrombolytic choice and sICH or any ICH. Conclusion Tenecteplase significantly reduced DNT and DPT. It was associated with early neurological function improvement (at 24 h), without compromising safety compared to alteplase. The findings support tenecteplase’s application in AIS.